Comprehensive Physiology 2013
DOI: 10.1002/cphy.c110062
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Insulin Resistance: Underlying Causes and Modification by Exercise Training

Abstract: Metabolic syndrome (MS) is a collection of cardiometabolic risk factors that includes obesity, insulin resistance, hypertension, and dyslipidemia. Although there has been significant debate regarding the criteria and concept of the syndrome, this clustering of risk factors is unequivocally linked to an increased risk of developing type 2 diabetes and cardiovascular disease. Regardless of the true definition, based on current population estimates, nearly 100 million have MS. It is often characterized by insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
466
0
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(494 citation statements)
references
References 750 publications
(928 reference statements)
10
466
0
18
Order By: Relevance
“…Studies assessing individual MetS components or insulin resistance as the cornerstone of MetS might help unveil the background of increased cardiometabolic risk in COPD patients and allow us to specifically target these factors. While the relative influence of lifestyle versus disease specific determinants and medication is still unclear, we know that exercise training may improve MetS in other risk populations (50). Pulmonary rehabilitation is an established intervention in COPD focusing on exercise training but the effects on modification of MetS is surprisingly not yet investigated in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing individual MetS components or insulin resistance as the cornerstone of MetS might help unveil the background of increased cardiometabolic risk in COPD patients and allow us to specifically target these factors. While the relative influence of lifestyle versus disease specific determinants and medication is still unclear, we know that exercise training may improve MetS in other risk populations (50). Pulmonary rehabilitation is an established intervention in COPD focusing on exercise training but the effects on modification of MetS is surprisingly not yet investigated in detail.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the adoption of such a policy in developing countries, an additional strategy by the WHO and International Society of Hypertension was developed by deriving both laboratoryand nonlaboratory-based CVD risk prediction charts for low-and medium-resource setings in countries in diferent WHO subregions. Signiicant researches have suggested that a vascular segment gives us a clue of atherosclerotic lesions, namely endothelial dysfunctions, macrophage activation, cellular proliferation and thrombosis, and they respond diferently on medication [8]. Therapeutic approach of the atherogenic dyslipidemia imposes the correlation with proatherogenic individual tendencies in order to correct the further risks [9].…”
Section: Recent Trends In Cardiovascular Risksmentioning
confidence: 99%
“…Development of insulin resistance (fasting serum insulin level of >25 mIU/l) is the major initial patho-physiological event responsible for mediating subsequent events and complications of metabolic syndrome. 2,3 Hyper-insulinemia induced due to decreased tissue sensitivity to insulin is responsible for sodium retention, sympathetic nervous system stimulation, vascular smooth muscle hypertrophy and oxidative stress. 2,3 Hence insulin resistance represents the mechanism or basis for development of hypertension in type-2 DM and vice-versa.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Hyper-insulinemia induced due to decreased tissue sensitivity to insulin is responsible for sodium retention, sympathetic nervous system stimulation, vascular smooth muscle hypertrophy and oxidative stress. 2,3 Hence insulin resistance represents the mechanism or basis for development of hypertension in type-2 DM and vice-versa. Major complication of metabolic syndrome in pre-diabetics is risk of onset of type-2 DM and in existing diabetics the higher incidences of cardiovascular related events like myocardial infarction, stroke etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation